2021
DOI: 10.1016/j.nmni.2021.100862
|View full text |Cite
|
Sign up to set email alerts
|

First detection of mobilized colistin resistance mcr-1 gene in Escherichia coli isolated from livestock and sewage in Iran

Abstract: Currently, few studies have investigated the mechanisms of resistance to colistin in Iran. The aim of this study was to investigate mcr -harbouring Escherichia coli dissemination in livestock and sewage in Iran. A total of 115 samples from cows ( n = 38), chickens ( n = 47) and urban sewage samples ( n = 30) were collected. The presence of genes including mcr1–6 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The MIC results showed that none of the isolates, even E. coli O25-B2-ST131 strains, were resistant to colistin, and colistin was the most effective antibiotic against E. coli isolates from UTI. Although a small number of colistin-resistant E. coli ST131 strains have been isolated from different samples in studies, colistin has still been identified as the most effective antibiotic in previous studies [2,51].…”
Section: Discussionmentioning
confidence: 99%
“…The MIC results showed that none of the isolates, even E. coli O25-B2-ST131 strains, were resistant to colistin, and colistin was the most effective antibiotic against E. coli isolates from UTI. Although a small number of colistin-resistant E. coli ST131 strains have been isolated from different samples in studies, colistin has still been identified as the most effective antibiotic in previous studies [2,51].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study was conducted in Iran, and for the first time, mcr-1 was detedcted in E. coli isolates rom livestock and wastewater (12). In a recent study, 37 (10.8%) colistin-resistant E. coli isolates were detected (MIC values >2 mg/L) and 36 fingerprint patterns were identified in colistin-resistant E. coli using ERIC-PCR (13)(Table 1).…”
Section: Iranmentioning
confidence: 99%
“…[ 7 ] Numerous risk factors have been enumerated to be linked with the incidence of gastrointestinal cancer, including red meat, alcohol, obesity, age, smoking, sex, and even infectious diseases like helicobacter pillory, and viral diseases. [ 6 7 8 9 10 11 12 13 ]…”
Section: Introductionmentioning
confidence: 99%